Handover adaptations for load balancing scheme in microcell / femtocell LTE network / Nurul Husna Md Yusoh - Md Yusoh, Nurul Husna (2013)
In the purpose of offering extensively higher data rates, higher systems throughput, and lower latency, the femtocell systems in 3 GPP LTE system has premeditate. In a large number of femtocells, there are too many prehandover and unnecessary handover processes frequently among femtocells may occur. Also, call failure due to handover may increase when the mobile moves from one serving cell to another cell. High number of switching load will occur due to the ping-pong effect. Handover procedures for existing networks are needed to support the macrocell/femtocell integrated network. This thesis proposes a modified handover procedure between macrocell and femtocell network. A handover algorithm is proposed based on Received Signal Strength (RSS) and speed of the User Equipment (UE) to improve the handovers between the macrocell and femtocell in LTE network. The result shows that unnecessary handover and handover failure can be optimized using modified handover in this macrocell and femtocell integrated network. Thus, the deployment of femtocell can increase the handover performance as well as offloading the macrocell traffic.